Akademiska mästerskap? - Ehn, Billy; Löfgren, Orvar (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2008)
This special issue is devoted to the new ways in which cultural research is evaluated, measured and ranked. What happens when the tools from the natural sciences of citation indexes and quantitative measurements are introduced into the humanities and social sciences? Our introduction discusses this impact and the problems of trying to translate styles of measurement and ranking between different academic traditions. There is often a silent knowledge, a kind of academic habitus, hidden in evaluations of research and excellence. We need to analyze and compare such different academic values and aesthetics of what constitutes good or bad research.